Tuberous Sclerosis - K. N. Monahov; O. L. Romanova; P. O. Amelina; K. Yu. Molodyh; Yu. S. Astahov; P. A. Nechiporenko; L. K. Atlasova (State Scientific Center of Dermatovenereology and Cosmetology, 2018)
Aetiology, pathogenesis, clinical and patomorphological criteria for diagnosis of tuberous sclerosis diagnosis are described in this paper. Clinical case of long undiagnosed tuberous sclerosis is presented.